Emotional anticipation after delivery – a longitudinal neuroimaging study of the postpartum period - Malin Gingnell (Nature Portfolio, 2017)
Abstract Neuroimaging research has begun to unveil the mechanisms behind emotion processing during the postpartum period, which, in turn, may be of relevance for the development of postpartum depression. The present study sought to longitudinally investigate the neural correlates of emotion anticipation during the postpartum period in healthy women. Functional magnetic resonance imaging was employed to measure the blood oxygen level-dependent signal in the brain in response to anticipation of negative emotional stimuli and during processing of images with positive or negative valence. The participating women were scanned twice: the first scan occurred during the first 48 hours after delivery, and the second was performed 4–6 weeks after delivery. The early postpartum period was characterized by higher anterior cingulate cortex reactivity during anticipation of negative emotional stimuli than the late postpartum period. This was accompanied by a negative relationship with insular reactivity during the early postpartum period and a trend towards an increase in insular reactivity in the late postpartum period. Thus, during the first four weeks of the postpartum period, a diminished top-down regulatory feedback on emotion-related areas of the brain was noted. This finding suggests a physiologically important adaptation during the healthy postpartum period.